TEACHER STRATEGIES IN TEACHING USING LEARNING MEDIA FOR PRIMARY SCHOOL STUDENTS - Novianti, Silfia; Triyogo, Agus (LP3MKIL, 2023)
This research aims to determine the mathematics learning difficulties of class V students at SD Negeri 59 to increase students' interest in learning in mathematics as well as to find out whether using learning media as a tool or strategy for teachers in teaching can handle the mathematics learning difficulties of class V elementary school students. The research used in this research is qualitative research where this research was carried out using three techniques, observation, interviews and documentation. In this study there were several students who experienced difficulties and lacked interest in Mathematics lessons. The results of the research show that using mathematics learning media can increase students' interest in learning mathematics in class V elementary school.